Thinking the South: Ideas, Music and Resistance Transatlantic Dialogues with Neo Muyanga - (:unkn) unknown (South African Sociological Association, 2024)
In July 2014, the Wits Institute for Social and Economic Research (WISER) organised the Johannesburg Workshop in Theory and Criticism on “Archives of the Non Racial”. 1 During two weeks, 60 intellectuals from all over the world got together on a bus trip around South Africa to think and reflect on race, class, gender and the legacies of colonialism in the Global South. It was during that trip that I met Neo Muyanga for the first time. A decade has passed since then, and over this time we became friends and tried to develop common projects that promoted South Atlantic links and debates between South Africa, Argentina, Uruguay and Brazil, among others. The publication of the following interview is a way to commemorate that precious academic and human event that impacted on all of us in very particular ways. This unique intellectual and academic network built in a bus across South Africa is still moving through the oceans and continents. Many of us are still in touch and looking for different ways of working together while creating bridges through disciplines and places of enunciation. Over the last 10 years, common projects have been held by members of the BUS that enabled new dialogues between local academics and students from South African, US, Brazilian, French, Dutch, English, Argentine and Indian universities, among others.

Efron, L. (2024). Thinking the South: Ideas, Music and Resistance Transatlantic Dialogues with Neo Muyanga. South African Review of Sociology, 54(3), 401-407.
Fil: Efron, Laura. University of the Free State; Sudáfrica
Fil: Efron, Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina
Keywords: Music; Slave Trade; Protest